Mechanical properties of ecological bricks formulated with civil construction waste - Ramos Muniz, Eduardo; Alves de Oliveira, Lorena (Seven Editora, 2023)
The soil-cement bricks, better known as ecological bricks represent an alternative fully in line with the guidelines of sustainable development because they require low power con-sumption in the extraction of raw materials, exempt the firing process and reduce the need for transport once the bricks are produced with the floor of the work site itself. The aim was to evaluate the use of construction waste in the production of ecological bricks. The bricks were manufactured basically by a mixture that consisted of soil, cement, and different per-centages of construction waste. The results were compared with current standards. Although the dosages of the bricks produced do not achieve the compression strength values required by NBR 10834 (1994), the addition of construction waste significantly improved characte-ristics of the same, both the water absorption, since only the witness received no the rate expected by NBR 10834 (1994), and the mass loss, all met the standard that is below 5%. DOI: 10.56238/pacfdnsv1-096